2014
DOI: 10.1002/jmv.24020
|View full text |Cite
|
Sign up to set email alerts
|

HPV prevalence and type distribution in women with normal or abnormal Pap smear in Bulgaria

Abstract: Human papillomavirus (HPV) is a well-known pathogen for lower genital tract neoplasias, yet little is known regarding HPV prevalence in Bulgaria. The aim of this study was to investigate the prevalence of HPV DNA and to determine HPV types distribution among women with normal and abnormal cytology. Cervical smears with different cytological diagnoses were collected from 355 Bulgarian patients. The cohort of patients selected is the biggest ever studied in this country. Using the Roche Linear Array HPV Genotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For example, HPV‐16, 18, 33, and 31 were detected in 52.2%, 18.3%, 14.5%, and 11.9% of women from Sofia with histologically proven dysplasia or cervical cancer, respectively . However, Grozdanov et al tested 355 patients with normal and pathological cytology and found that the two most prevalent genotypes were HPV‐16, detected in 61 samples, and HPV‐33, detected in 14 samples. Similarly, Todorova et al found that of 145 women with invasive cervical carcinoma, 98 (77.2%) were infected with HPV‐16 and 18, of which the former was more common and was found as a single infection in 86 (67.7%) samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, HPV‐16, 18, 33, and 31 were detected in 52.2%, 18.3%, 14.5%, and 11.9% of women from Sofia with histologically proven dysplasia or cervical cancer, respectively . However, Grozdanov et al tested 355 patients with normal and pathological cytology and found that the two most prevalent genotypes were HPV‐16, detected in 61 samples, and HPV‐33, detected in 14 samples. Similarly, Todorova et al found that of 145 women with invasive cervical carcinoma, 98 (77.2%) were infected with HPV‐16 and 18, of which the former was more common and was found as a single infection in 86 (67.7%) samples.…”
Section: Discussionmentioning
confidence: 99%
“…Bulgaria has not surveyed the nationwide prevalence of high‐, medium‐, and low‐risk cervical HPV genotypes in women as well as their distribution by age group . Indeed, all previous surveys of cervical HPV infection in the country were limited only to certain genotypes or to women with certain clinical, social, and geographic characteristics, such as those who work as prostitutes, are residents of Sofia, or were diagnosed with high‐grade squamous intraepithelial lesions, invasive cervical cancer, and abnormal cytology. Consequently, the available data are insufficient to assess the epidemiology of HPV among women in Bulgaria .…”
Section: Introductionmentioning
confidence: 99%
“…A Serbian study by Kovačević G. et al, 2016, including students from the University of Novi Sad found mixed HPV infection in 49.4% [30]. Relatively high rates of mixed HPV infection among the young population were also detected in the Bulgarian studies of Grozdanov P., 2014 (63.00%) [31] and Kovachev S., 2013 (53.00%) [32], as well as in the Romanian study of Moga M., 2014 (54.93%) [33].…”
Section: Discussionmentioning
confidence: 97%
“…A pioneer in the study of HPV in Bulgaria is Prof. Zl. Kalvachev, and a screening has been conducted by a number of researchers [ 11 , 12 , 13 ]. Papillomaviruses have oncogenic potential and are associated with the development of malignancies in humans and animals.…”
Section: Introductionmentioning
confidence: 99%